npj Sustainable Agriculture - Rodriguez, Daniel; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Sustainable Agriculture aims to become a global reference in the transition of agricultural systems towards more productive, environmentally sustainable, and equitable agri-food systems. The journal considers multi- and transdisciplinary, empirical, and in silico research approaches that produce actionable information or demonstrate positive impacts across the multiple functions of agriculture. The journal covers a broad range of topics that include: Sustainable agriculture from a production, food and nutrition security perspective (science and technology) Sustainable agriculture from an environmental and ecological perspective (planetary boundary) Sustainable agriculture from a policy and socio-economic perspective (interventions) Sustainability transitions in agricultural and food systems The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by agriculture experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Earth sciences; Geography; Agriculture; Earth and Environmental Sciences; Agriculture